Application of Transcranial Direct Current Stimulation in Neurorehabilitation: The Modulatory Effect of Sleep - Ebajemito, James K.; Furlan, Leonardo; Nissen, Christoph; Sterr, Annette (Frontiers in Neurology, 2016)
The relationship between sleep disorders and neurological disorders is often reciprocal, such that sleep disorders are worsened by neurological symptoms and that neurological disorders are aggravated by poor sleep. Animal and human studies further suggest that sleep disruption not only worsens single neurological symptoms, but may also lead to long-term negative outcomes. This suggests that sleep may play a fundamental role in neurorehabilitation and recovery. We further propose that sleep may not only alter the efficacy of behavioural treatments but also plasticity-enhancing adjunctive neurostimulation methods, such as transcranial direct current stimulation (tDCS). At present sleep receives little attention in the fields of neurorehabilitation and neurostimulation. In this review we draw together the strands of evidence from both fields of research to highlight the proposition that sleep is an important parameter to consider in the application of tDCS as a primary or adjunct rehabilitation intervention.